2019
DOI: 10.3390/su11133520
|View full text |Cite
|
Sign up to set email alerts
|

People Analytics of Semantic Web Human Resource Résumés for Sustainable Talent Acquisition

Abstract: The purpose of this study was to define a data science architecture for talent acquisition. The approach was to propose analytics that derive data. The originality of this paper consists in proposing an architecture to work within the process of obtaining semantically enriched data by using data science and Semantic Web technologies. We applied the proposed architecture and developed a case study-based prototype that uses analytics techniques for résumé data integrated with Linked Data technologies. We conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…Another aspect noticed by the researchers refers to the economic profitability of the project as a factor of extrinsic motivation reported to intrinsic motivation. Although rewards are an important incentive (Dikaputra et al, 2019 ), there is a wide variety of intrinsic incentives that determine individuals to get financially involved in supporting a project, such as peace of mind, altruism, reciprocity or benefits for the community via implementation of the projects (Yang et al, 2016 ; Necula and Strîmbei, 2019 ). Kuppuswamy and Bayus ( 2017 ) highlight the importance of prosocial behavior in the case of reward-based crowdfunding: the supporters of the projects wish to make a profit, while also contributing in turning an entrepreneur's idea into reality.…”
Section: Resultsmentioning
confidence: 99%
“…Another aspect noticed by the researchers refers to the economic profitability of the project as a factor of extrinsic motivation reported to intrinsic motivation. Although rewards are an important incentive (Dikaputra et al, 2019 ), there is a wide variety of intrinsic incentives that determine individuals to get financially involved in supporting a project, such as peace of mind, altruism, reciprocity or benefits for the community via implementation of the projects (Yang et al, 2016 ; Necula and Strîmbei, 2019 ). Kuppuswamy and Bayus ( 2017 ) highlight the importance of prosocial behavior in the case of reward-based crowdfunding: the supporters of the projects wish to make a profit, while also contributing in turning an entrepreneur's idea into reality.…”
Section: Resultsmentioning
confidence: 99%
“…According to the empirical equation, the number of neurons is in the range of [5,14]. Hence, the model with several neurons between [3,16] is trained and tested.…”
Section: Parameter Selectionmentioning
confidence: 99%
“…Abdullah et al (2020) designed an enterprise cloud-based HRMS with 16 standard modules to solve HR problems using the CodeIgniter Web framework, which was then launched and deployed on the Amazon Web Service elastic computing cloud and used for an efficient enterprise HRM [4]. Necula and Strı ˆmbei (2019) developed an architecture to semantically enrich data through data science and semantic web technology for talent training. The experimental results suggested that the classification effect of the proposed architecture was better than the commonly used regression analysis, Random Forest (RF), and Support Vector Machine (SVM), and the proposed architecture could effectively mark the resume data and use the semantic web to extract data information from the resume [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sabina-Cristiana Necula [12][13][14][15][16] defined a data science architecture that can analyze and derive the data for finding the right employee with good technical skills. The semantic web technologies extract the data that are specified in the resume and various skills are identified using the supervised machine learning algorithms.…”
Section: Related Workmentioning
confidence: 99%